Technology and modernization: urban transport developments in Valparaiso. 1850 - 1950 (Polis (Santiago), 2018)
The evolution of urban transport through a century in one of the cities with greatest technological transformations due to its port status closely linked to international trade is analyzed. This position facilitates the incorporation of major technological advances which are also part of the infrastructure that the city needs to carry out its economic activity in its external dimension. Indeed, the introduction of electricity in urban transport is an expression of a modernization process driven by the incorporation of such energy mode of the urban activity in Valparaíso. At the same time is brought to notice the geographic and social differences that present the city and its link to the access to transport, and therefore the process of modernization.
Keywords: urban transport; technological development; infrastructure